Management trade‐offs on ecosystem services in apple orchards across Europe: Direct and indirect effects of organic production. Issue 4 (12th November 2018) - Samnegård, Ulrika; Alins, Georgina; Boreux, Virginie; Bosch, Jordi; García, Daniel; Happe, Anne‐Kathrin; Klein, Alexandra‐Maria; Miñarro, Marcos; Mody, Karsten; Porcel, Mario; Rodrigo, Anselm; Roquer‐Beni, Laura; et al.
Abstract: Apple is considered the most important fruit crop in temperate areas and profitable production depends on multiple ecosystem services, including the reduction of pest damage and the provision of sufficient pollination levels. Management approaches present an inherent trade‐off as each affects species differently. We quantified the direct and indirect effects of management (organic vs. integrated pest management, IPM) on species richness, ecosystem services, and fruit production in 85 apple orchards in three European countries. We also quantified how habit composition influenced these effects at three spatial scales: within orchards, adjacent to orchards, and in the surrounding landscape. Organic management resulted in 48% lower yield than IPM, and also that the variation between orchards was large with some organic orchards having a higher yield than the average yield of IPM orchards. The lower yield in organic orchards resulted directly from management practices, and from higher pest damage in organic orchards. These negative yield effects were partly offset by indirect positive effects from more natural enemies and higher flower visitation rates in organic orchards. Two factors other than management affected species richness and ecosystem services. Higher cover of flowering plants within and adjacent to the apple trees increased flower visitation rates by pollinating insects and a higher cover of apple orchards in the landscape decreased species richness of beneficial arthropods. The species richness of beneficial arthropods in orchards was uncorrelated with fruit production, suggesting that diversity can be increased without large yield loss. At the same time, organic orchards had 38% higher species richness than IPM orchards, an effect that is likely due to differences in pest management. Synthesis and applications . Our results indicate that organic management is more efficient than integrated pest management in developing environmentally friendly apple orchards with higher species richness. We also demonstrate that there is no inherent trade‐off between species richness and yield. Development of more environmentally friendly means for pest control, which do not negatively affect pollination services, needs to be a priority for sustainable apple production. Abstract : Our results indicate that organic management is more efficient than integrated pest management in developing environmentally friendly apple orchards with higher species richness. We also demonstrate that there is no inherent trade‐off between species richness and yield. Development of more environmentally friendly means for pest control, which do not negatively affect pollination services, needs to be a priority for sustainable apple production. Editor's Choice